Autonomía universitaria y calidad de la enseñanza - Caviglia Marconi, Alessandro (2010)
Based on the historical fact that universities were created as autonomous institutions, this ¡¡rtide focuses on the relationship between excellence in higher education and university autonomy. At the same time, this article supports that excellence is achieved through the development of the fundamental values inherent to the university institution, such as academic excellence and public values of a constitutional democracy. Then it presents how política! indoctrination, religious fundamentalism, and the power of money are the three forces that seek to disempower universities. Since autonomy is what enables universities to develop their own values, it is necessary to defend them from these three forces.